Physically Modified Bacterial Cellulose Biocomposites for Dental Materials Scaffolds - Olyveira, Gabriel Molina de [UNESP]; Riccardi, Carla dos Santos [UNESP]; Santos, Marcio Luiz dos [UNESP]; Manzine Costa, Ligia Maria; Daltro, Paula Braga [UNESP]; Basmaji, Pierre; Daltro, Gildasio de Cerqueira; Guastaldi, Antonio Carlos [UNESP] (Amer Scientific Publishers, 2015)
Bacterial cellulose (BC) has become established as a remarkably versatile biomaterial and can be used in a wide variety of scientific applications, especially for medical devices. In this work, the bacterial cellulose fermentation process was modified by the addition of hyaluronic acid (1% w/w) to the culture medium before the bacteria is inoculated. Besides, the potential of gamma irradiation treatment for the modification of the BC surface properties, enhancing its potential for biomedical applications was also analyzed. Finally, biomimetic precipitation of calcium phosphate (CaP) of biological interest from simulated body fluid on bacterial cellulose was evaluated for perspectives in dental materials scaffolds applications. The effect of the addition of hyaluronic acid on bacterial cellulose was analyzed using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA), as well as after CaP coatings produced by biomimetic route. FTIR analysis showed interaction between bacterial cellulose nanobiocomposites and calcium phosphate, XRD demonstrated amorphous calcium phosphate and sodium chloride on bacterial cellulose nanobiocomposites and samples showed significant variation in thermal properties.
Keywords: Bacterial Cellulose; Nanoskin (R); Nanocomposites; Scaffolds; Dental Materials